The Use Virtual Reality to Assist In The Preparation Of An Ergonomic Analysis Of Nuclear Facilities - Daniel Mol Machado; Antonio Carlos de Abreu Mól; Andre Cotelli do Espírito Santo; Mario Cesar Vidal; Celso Marcelo Franklin Lapa (Brazilian Journal of Radiation Sciences)
Ergonomic Analysis consists of making value judgments about the global performance of certain man-machine or man-task systems and may result from a demand related to conditions and/or safety at work. However, during the performance of the Ergonomic Analysis, the presence of ergonomists can interfere with the work progress, which limits the observation time. Organizations that have risk areas have already been using simulated exercises to train their professionals. With the use of simulation tools, it becomes increasingly necessary to develop methods and techniques that allow the performance of this training, as close as possible to real work activities. In this context, this article proposed to create and verify if the use of Virtual Reality can help the Ergonomic Analysis of Work, developing scenarios and virtual simulation environments, contextualized by the Ergonomics perspective. For this purpose, a case study was carried out at the Institute of Nuclear Engineering where the Ergonomic Work Analysis and the modeling of the virtual environment were carried out. Finally, from the results presented, it can be concluded that Virtual Reality serves as a complementary tool to assist the ergonomist in the Ergonomic Analysis process, allowing him to use the tool to reduce risks, saving time and improving his performance.